Menggunakan Story Telling dalam Meningkatkan Kemampuan Speaking Mahasiswa - Andriani, Desi; Anggraini , Dian; Afersa, Mona (Fakultas Sastra Universitas Ekasakti, 2025)
Story telling is one of the techniques in improving students’ speaking skill. Through story teling, students can express some characters such as sad, happy, angry and others. The research is descriptive research. The population of the research is students of Universitas Putra Indonesia Padang. The sample is students of English education of teacher training faculty of Universitas Putra Indonesia YPTK Padang. The result shows that story-telling is very suitable to increase students’ speaking skill